Method of template hiding data in vector images - Ковтун, Владислав Юрійович; Кінзерявий, Олексій Миколайович; Стокіпний, Олександр Леонідович (Ukrainian Information Security Research Journal, 2014)
In this work authors propose the new steganographicmethod of template hiding data in vector image structure.According to the proposed method, hiding data is performedby the gradually separation of Bezier curves intovisually identical pluralities of segments with using preassignedcorrelation table of the different values of templateelements with the different steps of Bezier curves structure.There was conducted the software implementationof proposed method of hiding information in vector imagesof SVG format. The obtained results of experimentwere compared with the results of existing bitwise methodof hiding data in Bezier curves. The proposed methodshowed the profit (in more than 2 times) in reduction ofsteganocontainer size and time, required for hiding data inSVG image structure.